The Greek public discourse on immigration: The merchants of conditional humanism - Poulakidakos, Stamatis Nikitas (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2018)
Theoretically stemming from the notions of risk society and the politics of fear, this paper seeks to address issues related to the representations of immigrants in Greece through the public discourse, as it appears in the sites of two mainstream Greek daily newspapers. We examine specific parameters of the discourse related to refugees/immigrants (provision -or not- of asylum or other civil rights, provision -or not- of humanitarian aid, effects of migrant/refugees on public finance, on public health and social life of host communities, and their influence to the culture of the host societies). Quantitative content analysis of the statements on the conditional provision of humanitarian aid to the refugees/immigrants documented an overall representation of immigrants mainly as poor, uprooted, marginal, desperate and therefore somehow inferior to the members of the host societies and as ”risks” that needs to be managed.